2008
DOI: 10.1002/bit.22104
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetic force‐based cell patterning for controlling cell–cell interactions in angiogenesis

Abstract: To investigate the effects of cell-cell interactions on cellular function, the microenvironment surrounding cells should be precisely controlled. Here, we describe a cell patterning technique, which utilizes magnetic force and magnetite nanoparticles. This method was used to develop cell culture arrays for investigation of cell behaviors in angiogenesis. Pin holder devices that contain more than 6,000 pillars on the surface are used for fabricating the cell culture arrays by setting it on a magnet. The magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…[6][7][8] Numerous studies have also indicated that mechanical forces can regulate gene expression. [9][10][11][12] There are feedback loops incorporating cancer malignancy and metastasis, 17,18 blood vessel angiogenesis, [19][20][21][22] bone growth and osteoporosis and lung, heart and skeleton muscle metabolism.…”
Section: Mechanical Force and Biologymentioning
confidence: 99%
“…[6][7][8] Numerous studies have also indicated that mechanical forces can regulate gene expression. [9][10][11][12] There are feedback loops incorporating cancer malignancy and metastasis, 17,18 blood vessel angiogenesis, [19][20][21][22] bone growth and osteoporosis and lung, heart and skeleton muscle metabolism.…”
Section: Mechanical Force and Biologymentioning
confidence: 99%
“…18,19 Array patterns of microparticles or cells have been utilized in the design of biosensors, as scaffolds for patterning proteins, and in cell cultivation. In recent years, various techniques for manipulating bioparticles on chips have been developed using hydrodynamics, 1,73 magnetic forces, [74][75][76][77][78][79][80] and DEP. 16,17,81-85 DEP was first described by Pohl as the motion of dielectric particles under the influence of a non-uniform electric filed.…”
Section: Dep-based Devices For Bioanalysismentioning
confidence: 99%
“…The physical manipulation of biological particles is a vital component of miniaturized biotechnological platforms such as ''lab-on-a-chip'' devices and arrays for high-throughput assays. In recent years, many techniques regarding the manipulation of bioparticles on chips have been developed using hydrodynamics (El-Ali et al, 2006;Peterson 2005;Yang et al, 2007), magnetic forces (Ino et al, , 2009Ito et al, 2007Ito et al, , 2005Tsuchiya et al, 2008), dielectrophoresis (DEP) (Albrecht et al, 2006(Albrecht et al, , 2007Bocchi et al, 2009;Hsiung et al, 2008;Kim et al, 2007;Lee et al, 2008;Suzuki et al, 2004Suzuki et al, , 2007Suzuki et al, , 2008Taff and Voldman, 2005;Tornay et al, 2008;Wang et al, 2007;Yantzi et al, 2007;Yasukawa et al, 2007), electrophoresis , and pneumatic force (Hiranishi et al, 2007;Jeong and Konishi, 2009).…”
Section: Introductionmentioning
confidence: 99%